Pantoprazole induced black hairy tongue: a case report - Krishnan, Divya G.; Keloth, Anukesh Vasu; P., Neethu (International Journal of Basic & Clinical Pharmacology, 2023)
Black hairy tongue (BHT) is characterized by abnormally hypertrophied and elongated filiform papillae, appearing as blackish discoloration on the dorsal surface of the tongue. BHT has been reported as an adverse drug reaction to different categories of drugs. However, pantoprazole induced BHT has been rarely reported. We present the case of a 42-year-old female, admitted in the surgery ward with postoperative wound infection, for which she was prescribed oral clarithromycin and pantoprazole. On the third day of starting medications, she complained of blackish discoloration on the dorsal surface of the tongue with an alteration of taste sensation, which was clinically and microscopically diagnosed as BHT. Suspecting BHT as an adverse drug reaction to pantoprazole, it was stopped, while clarithromycin was continued for the full course. She was also advised to scrape her tongue thrice daily, drink adequate fluids and maintain good oral hygiene. On the third day after stopping pantoprazole, black discoloration and alteration of taste sensation resolved completely. WHO-UMC causality assessment scale showed a ‘probable’ association of the adverse drug reaction with pantoprazole. Physicians should be aware of the possibility of BHT with the use of pantoprazole and that it completely resolves on stoppage of the drug, mechanical debridement and good oral hygiene.